Tantangan Dalam Mengembangkan Komunikasi Lingkungan Pada Isu Sampah Plastik - Eko Budi Pratama; Pramilania Oktavia (Institut Nalanda, 2024)
In SIPSN KLHK data, plastic waste in Indonesia has significantly increased over the last three years, indicating a growing level of public awareness about the issue. The objective of this article is to achieve optimal environmental communication by describing the challenges in developing environmental communication on the issue of plastic waste, both conventionally and digitally. This aims to serve as a comprehensive review regarding challenges that have not been discussed by previous researchers who did not specify environmental communication challenges related to plastic waste. The research method used is qualitative, utilizing data collection techniques such as interviews, observations, and literature reviews. The interviews and observations were conducted at Bank Sampah Teratai, a waste bank in South Tangerang City. The findings reveal that the challenges in developing environmental communication on plastic waste can be categorized by media (digital and conventional), demographic age groups (teenagers, adults, and seniors), and administrative challenges, all analyzed using Lasswell's theory of communication elements. In conclusion, the primary factors contributing to these challenges are inconsistency and public skepticism. The urgency of this research is the increasing volume of plastic waste annually, which has significant environmental impacts. Therefore, enhancing public awareness about plastic waste through effective environmental communication is crucial. The researcher recommends that environmental communicators focus on addressing solutions to inconsistency and skepticism to mitigate these challenges.